PENERAPAN METODE NORTH WEST CORNER, LEAST COST, DAN VOGEL’S APPROXIMATION UNTUK MENGOPTIMALKAN BIAYA TRANSPORTASI PADA DISTRIBUSI PANEL SURYA KE SETIAP LOKASI PROYEK - Sapna, Sopyan; Iriani, Yani (LPPM Universitas Bina Bangsa, 2025)
PT XYZ adalah perusahaan konstruksi dan engineering untuk Pembangkit Listrik Tenaga Surya (PLTS). The company has difficulty because the delivery of solar panels from the warehouse where they operate is not efficient enough to the project location, because the project in Banten, West Java, Central Java, and East Java. Using the three methods (North West Corner, Least Cost, and Vogel's Approximation) optimal solutions will be obtained to minimize transportation costs. The analysis shows that Vogel's Approximation method is the best result with the total cost of transportation equal to IDR 318,391,711, cost savings value of IDR 63,906,369 or 16.72% compared to the real cost faced is IDR 382,298,080. Overall, these results suggest that using transport optimization methods for such operations can lead to considerable cost savings and enhanced efficiency in solar panel delivery. This research is anticipated to help PT XYZ in determining the distribution of solar panels that can be more efficient as well as cost-effective in any of PT XYZ future projects